Egy hosszútávú küldetés: a Hármas Kötél Családközpont bemutatása - PÁL, Tünde (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2019)
A Long-Term Mission – Presentation of the Hármas Kötél Családközpont (Three Ropes Family Centre). Based on the experience of the marriage preparation programme of the Unitarian Church in Sfântu Gheorghe, we have created the Hármaskötél Családközpont (Three Ropes Family Centre), which is trying to answer the challenges of the trans-formation of marriage and religion through its programmes and groups. We are convinced that family is the most appropriate institution for transmitting the values and building up society. On this basis, our aim was to create a new service model, which is capable of strengthening families and transmitting the family spirituality. However, we assume that being connected to the families is also an active missionary activity, the active manifestation of religiosity, in which the missionary strength consists of paying attention, empathy, help, namely the service. The essay deals with the social phenomenon defining the need for founding the Hármaskötél Családközpont (Three Ropes Family Centre) and the practical questions concerning the organisation of its groups.